Nachhaltigkeitsmanagement und Nachhaltigkeitsberichterstattung öftentlicher Unternehmen. - (:unkn) unknown (Nomos, 2015)
Obgleich Öffentliche Unternehmen traditionell eine besondere Affinität zu Fragen des Nachhaltigkeitsmanagements aufweisen, liegen bisher nur wenige Informationen vor, wie deren Nachhaltigkeitsmanagement ausgestaltet und organisatorisch verankert ist, welche Ziele mit ihm verfolgt werden, wie die Berichterstattung erfolgt und wie der Erfolg des Nachhaltigkeitsmanagements gemessen wird. Der Arbeitskreis "Nachhaltigkeit in der öffentlichen Wirtschaft" des Wissenschaftlichen Beirats des Bundesverbandes Öffentliche Dienstleistungen (bvöd) legt die Ergebnisse seiner bislang rund zweijährigen Beschäftigung mit dem Thema vor.

One key element of public sector reforms has been strengthening the entrepreneurial way of public service delivery. Entrepreneurship is seen as an appropriate way of enhancing the impact of public policies and increasing the effectiveness and efficiency of the public sector. Connected with this is the expectation that the entrepreneurial mode of public service deliveries transforms public sector entities into more flexible entities which are more responsive to their constituencies (and taxpayers ) needs. These assumptions served as a motivation to compare internationally the experiences with public entrepreneurship on the following levels: understanding of public entrepreneurship, types of public entrepreneurship and areas of activity. Conceptual and empirical findings from Austria, Botswana, Canada, Estonia, Germany, Japan and the United States are presented in this special issue. The best and bad practices show that public entrepreneurship is a complex but worthwhile endeavour.
Keywords: Wirtschaftspolitik; Öffentliches Unternehmen; Management; Öffentlichkeitsarbeit; Nachhaltigkeit